Pulmonary adverse events associated with hypertension in non-small cell lung cancer patients receiving PD-1/PD-L1 inhibitors - Chen, Jianing; Wen, Yaokai; Chu, Xiangling; Liu, Yuzhi; Su, Chunxia (Frontiers in Pharmacology, 2022)
Introduction: Non-small cell lung cancer patients have gained therapeutic benefits from immune checkpoint inhibitors, although immune-related adverse events (irAEs) could be inevitable. Whether irAEs are associated with chronic diseases is still unclear, our study aims to clarify the distinct adverse events in NSCLC patients with concomitant hypertension. Methods: Adverse event cases were searched and collected in the Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database from January 2015 to December 2021. We performed disproportionality analysis to detect safety signals by calculating reporting odds ratios (ROR) and corresponding 95% confidence intervals (95% CIs), information component (IC), and the lower bound of the information component 95% credibility interval (IC025). Results: Among 17,163 NSCLC patients under treatment with single-agent anti-programmed death-1/programmed death ligand-1 (PD-1/PD-L1) inhibitor (nivolumab, pembrolizumab, cemiplimab, durvalumab, atezolizumab, and avelumab), 497 patients had hypertension while 16,666 patients had no hypertension. 4,283 pulmonary AEs were reported, including 166 patients with hypertension and 4,117 patients without hypertension. Compared with patients without hypertension, patients with hypertension were positively associated with increased reporting of interstitial lung disease (ROR = 3.62, 95%CI 2.68–4.89, IC = 1.54, IC025 = 0.57) among patients receiving anti-PD-1 treatment. The median duration of onset from the time of initiation of anti-PD-1 administration was 28 days (IQR, 12.00–84.25). Conclusion: Our pharmacovigilance analysis showed the profile of pulmonary toxicities in NSCLC patients with hypertension caused by anti-PD-1/PD-L1 inhibitors. Interstitial lung disease was the statistically significant reporting adverse event in patients with hypertension receiving anti-PD-1 treatment.